Energy efficient cache invalidation in a disconnected wireless mobile environment. (7th December 2006) - Chand, Narottam; Joshi, Ramesh Chandra; Misra, Manoj
Caching of frequently accessed data on the mobile clients can reduce the number of uplink requests, server load and query latency and can increase data availability. As cached data items eventually become invalid due to updates at the server, an invalidation strategy is employed to maintain cache consistency so that no obsolete data would be used to serve queries. The basic cache invalidation strategies make use of periodic invalidation reports (IRs) and updated invalidation reports (UIRs) broadcast by the server. This paper presents a synchronous stateful caching strategy called update report (UR). UR strategy preserves the advantages of IR/UIR strategies and improves on their disadvantages. It reduces the size of IR by filtering out noncached items, handles long disconnection, reduces query latency by broadcasting recently requested items immediately after every UIR, conserves client energy and supports mobility. Simulation results prove that UR yields better performance than IR and UIR strategies.